2012
DOI: 10.2741/e518
|View full text |Cite
|
Sign up to set email alerts
|

The thermoneutral zone implications for metabolic studies

Abstract: Introduction 2.1. Definition of thermoneutral zone 2.2. Thermoneutral zone across studies 2.3. Heat balance in the thermoneutral zone 2.3.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 87 publications
(144 reference statements)
3
97
0
5
Order By: Relevance
“…Curiously, deficiencies in the oxytocin receptor gene have been associated with problems in the development of BAT in mice (Takayanagi et al, 2008). We thus think that BAT, seen as important for thermogenesis, could even play a role in determining meaningful psychological individual difference patterns, and that a place to examine this is in individual difference patterns of people's thermoneutral zones (Kingma et al, 2012(Kingma et al, , 2014.…”
Section: Formation Of the Predictive Modelmentioning
confidence: 99%
“…Curiously, deficiencies in the oxytocin receptor gene have been associated with problems in the development of BAT in mice (Takayanagi et al, 2008). We thus think that BAT, seen as important for thermogenesis, could even play a role in determining meaningful psychological individual difference patterns, and that a place to examine this is in individual difference patterns of people's thermoneutral zones (Kingma et al, 2012(Kingma et al, , 2014.…”
Section: Formation Of the Predictive Modelmentioning
confidence: 99%
“…Part of this effect can be attributed to reproductive hormones and the menstrual phase. In general, relative to men, the thermoneutral zone of women is shifted upward (the temperature range at which the person feels 'comfortable') 56) . When comparing the sexes, it has been observed that women tolerate humid heat better as females are superior in suppressing excess sweating and therefore conserve body water.…”
Section: Individual Aspectsmentioning
confidence: 99%
“…Except for the operative temperatures of 21°C and 24°C where the two confidence intervals overlap, other operative temperatures have observed significantly different clo values (p < 0.05) between males and females, with females generally 0.1 to 0.2 higher than males. Theses results may be driven by the higher cold sensitivity that women usually demonstrate, as reported in several comfort studies (NAKANO; TANABE; KIMURA, 2002;MORGAN;DE DEAR, 2003;KINGMA; FRIJNS; VAN MARKEN LICHTENBELT, 2012;SCHELLEN et al, 2012). The higher variability in women's dresses that are discussed previously could also contribute to this difference.…”
Section: Gender and Age Groups Differences In Clo Valuesmentioning
confidence: 64%